The Effect of Servant Leadership, Organizational Culture and Social Capital on Employee Performance at the Social Services Office of North Toraja Regency (International Journal of Economics and Management Research, 2025)
This study aims to analyze the influence of servant leadership, organizational culture, and social capital on employee performance at the Social Services Office of North Toraja Regency. The research employed a quantitative approach using a survey method. The population consisted of all 37 employees of the Social Services Office, and the entire population was selected as the sample through a saturated sampling technique. Data were collected using questionnaires as the primary instrument, supported by interviews and observations to strengthen the validity of the findings. The collected data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The results revealed that servant leadership did not have a positive and significant effect on employee performance, as indicated by the calculated t-value of 0.965, which was lower than the t-table value, and a significance level above 0.05. Organizational culture also showed no positive and significant effect on employee performance, with a calculated t-value of 0.929, suggesting that existing values, norms, and work habits had not significantly contributed to performance improvement. In contrast, social capital demonstrated a positive and significant influence on employee performance, as indicated by a calculated t-value of 4.415, showing that trust, cooperation, and harmonious relationships among employees supported better performance. Simultaneously, servant leadership, organizational culture, and social capital collectively had a significant effect on employee performance. Therefore, strengthening service-oriented leadership, building a supportive organizational culture, and enhancing social capital are important strategies for improving employee performance and public service quality.